Morphological Analysis of the Spiral Structure of Interacting Galaxies (2023)
This research focused on the study of multiple spiral structures in galaxies undergoing various types of interactions, with a specific emphasis on galaxies NGC 4254 and NGC 5985. Using the two-dimensional Fourier transform, the study provides insights into the complex morphological features of these galaxies. NGC 4254, classified as SA(s)c, reveals prominent m = 1 and m = 2 modes in the Fourier analysis, indicating continuous spiral structures extending from the nucleus to the outer regions. In the case of NGC 5985, classified as SAB(r)b, the dominant Fourier modes are m = 1 and m = 2. The study measured the length of the bar to be 3.9 kpc and a ring with a radius of 10.9 kpc. The presence of discontinuous spiral structures is attributed to numerous bifurcations in the spiral arms. In summary, this research provides valuable insights into the nature of multiple spiral structures in interacting galaxies. The two-dimensional Fourier transform proves to be a valuable tool for uncovering morphological details, offering key insights into the evolutionary histories and environmental influences of NGC 4254 and NGC 5985.